Multiple Gestation after Elective Single-Embryo Transfer: A State-of-the-Art Review of Literature and Suggested Mechanisms - Mokhamad Zhaffal; Rania Al Jafari; Anastasia Salame (Hindawi Limited, 2024)
Background. Elective single-embryo transfers are being increasingly used to curb the increase in multiple gestation rates. However, it has been documented that single-embryo transfers could still result in twins and on rarer occasions in triplet pregnancies. Main Body. A literature review was done to highlight the possible mechanisms leading to embryonic splitting. In this review, the incidence of zygotic splitting was addressed and the notion of chorionicity was explained. Risk factors for zygotic splitting and suggested mechanisms for both twin and higher order pregnancies were suggested and discussed. Conclusion. The hypotheses that we have so far remain unproven due to the rarity of zygotic splitting as well as the ethicolegal considerations of human embryo research. The presence of such incidents necessitates extensive counselling of the couple.